2010
DOI: 10.1016/j.bone.2009.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sexual dimorphism in femora of the eusocial and hypogonadic naked mole-rat: A novel animal model for the study of delayed puberty on the skeletal system

Abstract: Sex steroid hormones are major determinants of bone morphology and quality and are responsible for sexually dimorphic skeletal traits. Hypogonadism results in suboptimal skeletal development and may lead to an increased risk of bone fracture later in life. The etiology of delayed puberty and/or hypothalamic amenorrhea is poorly understood, and experimental animal models addressing this issue are predominantly based upon short-term experimental induction of hormonal suppression via gonadotropin releasing hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 58 publications
4
56
0
Order By: Relevance
“…We questioned whether previous reports of neotenous traits in NMRs indicate a failure to mature, associated with delayed reproduction in subordinates (Jarvis, 1981; Pinto et al, 2010), or simply a difference in developmental heterochrony when compared to similar-sized rodents. Unlike commonly studied laboratory mice and rats, which complete brain maturation by 3 and 6 weeks of age, respectively, we found that NMR brain development tracks more closely with long-lived species (e.g., humans and non-human primates).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We questioned whether previous reports of neotenous traits in NMRs indicate a failure to mature, associated with delayed reproduction in subordinates (Jarvis, 1981; Pinto et al, 2010), or simply a difference in developmental heterochrony when compared to similar-sized rodents. Unlike commonly studied laboratory mice and rats, which complete brain maturation by 3 and 6 weeks of age, respectively, we found that NMR brain development tracks more closely with long-lived species (e.g., humans and non-human primates).…”
Section: Discussionmentioning
confidence: 93%
“…This has been attributed to their retained expression of a neonatal NMDA receptor subunit that is less sensitive to hypoxic conditions (Peterson et al, 2012a,b). Other neotenous traits include unfused growth plates in bone (Pinto et al, 2010), immature lung morphology (Maina et al, 1992). Moreover, many of the described NMR brain features are suggestive of an extended period of development or persistent neoteny as well.…”
Section: Introductionmentioning
confidence: 99%
“…Despite femora reaching higher bone compactness than the humerus, a systemic genetic regulation for bone thickening is more plausible rather than mechanical stimulation of a single limb (forelimb). In addition, non‐reproductive colony members born in captivity of the eusocial Heterocephalus glaber , still develop thick cortical bone walls before reaching sexual maturity . This information suggests that genetic factors are more likely to influence the development of cortical bone thickening in Bathyergus and other bathyergids.…”
Section: Discussionmentioning
confidence: 99%
“…16 Examples of these virtually unchanged parameters include basal metabolic rate; vascular health and relaxation; bone and cartilage integrity and mineral density; ROS production, antioxidant activity, and oxidative damage; glucose tolerance; and glycated hemoglobin. 3,19,22,32,60,74,82,100 Current studies are examining the stability of the genome and proteins with age. 58,101 For example, sustained high levels of neuregulin-1 were documented in aged NMRs, suggesting that one mechanism of longevity is stability of neuregulin signaling and sustained brain function.…”
mentioning
confidence: 99%